1997
DOI: 10.1046/j.1365-2036.1997.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal intragastric acidity after over‐the‐counter doses of famotidine, ranitidine or placebo

Abstract: Aim: To compare the inhibitory effects of over‐the‐counter doses of famotidine or ranitidine on nocturnal intragastric acidity in a placebo‐controlled study. Methods: Twelve‐hour intragastric acidity was measured simultaneously in 24 healthy subjects who ate a standard meal at 18.30 h and were dosed (at 19.30 h) with either famotidine 10 mg, ranitidine 75 mg or placebo in a balanced three‐period crossover design. Five‐millilitre aliquots of gastric juice were aspirated half‐hourly 0–3 h post‐dose, and then hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In this study, the gastric acid inhibitory effect of ranitidine, 75 mg, and famotidine, 10 mg, taken around midday, persisted even in the overnight period. Overall, the effects of ranitidine and famotidine were similar and consistent with previous studies which have evaluated low doses of famotidine and ranitidine 3–6 , . 16 However, it is uncertain whether this late and modest effect can translate into symptomatic benefit for patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the gastric acid inhibitory effect of ranitidine, 75 mg, and famotidine, 10 mg, taken around midday, persisted even in the overnight period. Overall, the effects of ranitidine and famotidine were similar and consistent with previous studies which have evaluated low doses of famotidine and ranitidine 3–6 , . 16 However, it is uncertain whether this late and modest effect can translate into symptomatic benefit for patients.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have compared the onset and duration of action of ranitidine, famotidine and cimetidine on intragastric acidity using the model of 24‐h acidity 3–6 . This model was designed for the study of the effect of these drugs on gastric acidity by attempting to simulate normal everyday activity.…”
Section: Introductionmentioning
confidence: 99%
“…30 In this situation, taking the H 2 -antagonist after the last meal is recommended. Grimley et al 10 found no signi®cant difference in the ef®cacy of these drugs on nocturnal intragastric acidity.…”
Section: Discussionmentioning
confidence: 97%
“…Studies comparing the efficacy of the H 2 ‐antagonists at over‐the‐counter dosage were usually performed either in fasting or postprandial subjects 6 –11 . It is well known that meal intake reduces the acid inhibitory effect of high dose H 2 ‐antagonists 12 –14 .…”
Section: Introductionmentioning
confidence: 99%
“…Over-the-counter H2RAs doses (ranitidine 75 mg, famotidine 10 mg), are less than those listed in the prescription product insert, however, at these doses they are effective in reducing overnight gastric acidity for 12 h [61], as well as blunting the food-stimulated gastric response [62,63]. They are also effective in the treatment of symptomatic GERD [47].…”
Section: Drugs Modulating Gastric Acidmentioning
confidence: 99%